Female and immature stages of Oukuriella epleri Messias & Fittkau, 1997, a freshwater sponge-dwelling Chironomidae - Roque, Fabio O. (Aquatic Insects, 2020)
Female, pupa, and larva of Oukuriella epleri Messias & Fittkau, 1997 are described and figured. The larvae were collected in freshwater-sponges from Amazonia. We also provide an emended diagnosis for the genus. © 2007 Taylor & Francis.